Rendahnya Partisipasi Mahasiswa dalam Organisasi Kemahasiswaan dan Implikasinya bagi Pendidikan Kepemimpinan di Universitas Islam Negeri Sumatera Utara - Syarina Suhilah Siregar; Hasan Bakti Nasution; Mardian Idris Harahap (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2026)
Declining student participation in student organizations at the State Islamic University of North Sumatra has become a concern because these organizations play a vital role in character building, social skill development, and leadership education. This study analyzes the level of student participation, identifies the factors contributing to low participation, and examines its implications for leadership education. A descriptive qualitative approach was employed using interviews, observation, and documentation involving 20 informants, including active, semi-active, and inactive students as well as student organization administrators. The findings reveal that student participation remains low to moderate due to high academic workloads, the dominance of digital technology, limited organizational interest, weak leadership development, economic constraints, and poor time management. These factors weaken leadership regeneration and reduce opportunities for developing leadership competencies. This study contributes to the higher education literature by demonstrating that improving leadership education requires adaptive organizational governance and inclusive cadre development, rather than relying solely on student motivation. Therefore, strengthening cadre development, innovating organizational programs, utilizing social media effectively, and fostering an inclusive organizational environment are essential to increasing student participation and leadership development.